2023
DOI: 10.3390/jmse11112122
|View full text |Cite
|
Sign up to set email alerts
|

Sloshing Response of an Aquaculture Vessel: An Experimental Study

Yanwu Tao,
Renqing Zhu,
Jiayang Gu
et al.

Abstract: The sloshing response is crucial to the design and operation of aquaculture vessels and affects the safety of the culture equipment and the efficiency of the culture operation. A 1/50 scaled model was utilized to investigate the coupled sloshing response characteristics of a novel aquaculture vessel in a wave basin. Two wave directions (beam and head wave) and two filling levels (81.5% and 47.4%) are taken into account. The time-domain and frequency-domain characteristics of the sloshing response under the lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…∆ is expressed as ∆ = ln(ξ 1 /ξ k ), where ξ 1 is the wave amplitude of the first free damping cycle, ξ k is the wave amplitude of the subsequent free damping n cycle, and k is the number of the free damping cycle. Such an approach was employed in the 2D free surface sloshing experiments of Simonini et al [27] and Bäuerlein and Avila [28] and in the 2D separation surface sloshing experiments of Liu et al [11,12], in which they demonstrated that the decay of the transient planar wave has an exponential form ξ = ξ 1 e (−δt) . However, in 3D free surface or separation surface rotary sloshing experiments, the calculation of the viscous damping rate δ is intricate and requires careful consideration.…”
Section: Determination Of the Damping Rate And Natural Frequencymentioning
confidence: 99%
See 1 more Smart Citation
“…∆ is expressed as ∆ = ln(ξ 1 /ξ k ), where ξ 1 is the wave amplitude of the first free damping cycle, ξ k is the wave amplitude of the subsequent free damping n cycle, and k is the number of the free damping cycle. Such an approach was employed in the 2D free surface sloshing experiments of Simonini et al [27] and Bäuerlein and Avila [28] and in the 2D separation surface sloshing experiments of Liu et al [11,12], in which they demonstrated that the decay of the transient planar wave has an exponential form ξ = ξ 1 e (−δt) . However, in 3D free surface or separation surface rotary sloshing experiments, the calculation of the viscous damping rate δ is intricate and requires careful consideration.…”
Section: Determination Of the Damping Rate And Natural Frequencymentioning
confidence: 99%
“…The sloshing of the free liquid surface has motivated an enormous number of theoretical, experimental, and numerical studies [9][10][11][12]. A summary of the relevant investigations performed in the past few decades is available in Ibrahim [13], Faltinsen and Timokha [6], Ibrahim [7], and Igbadumhe and Furth [14].…”
Section: Introductionmentioning
confidence: 99%